2016
DOI: 10.5539/gjhs.v8n11p320
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Mean Platelet Volume in Acute Myocardial Infarction vs. Normal Coronary Angiography

Abstract: Considering the importance of cardiovascular disease and the role that platelets have in thrombosis formation in the coronary arteries, this study was done in order to assess platelet-related indices in patients who suffered acute myocardial infarction (MI) and compare them with those who had normal coronary angiography results.In this descriptive-analytical study, 200 patients who were admitted to our university hospital due to chest pain were included. The patients were divided into five groups including ST-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
0
0
1
Order By: Relevance
“…The mean of MPV was found to be higher in the patient without dyslipidemia compared to patients with dyslipidemia, but the difference was not statistically significant (p = 0.919). This is not following the study by Rai et al (2016), which found the mean of MPV was higher in patients with dyslipidemia. The MPV in smokers was higher than in non-smokers but was insignificant (p = 0.632).…”
Section: Resultscontrasting
confidence: 71%
“…The mean of MPV was found to be higher in the patient without dyslipidemia compared to patients with dyslipidemia, but the difference was not statistically significant (p = 0.919). This is not following the study by Rai et al (2016), which found the mean of MPV was higher in patients with dyslipidemia. The MPV in smokers was higher than in non-smokers but was insignificant (p = 0.632).…”
Section: Resultscontrasting
confidence: 71%